2014
DOI: 10.7314/apjcp.2014.15.5.2345
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein Interaction Network Analyses for Elucidating the Roles of LOXL2-delta72 in Esophageal Squamous Cell Carcinoma

Abstract: Lysyl oxidase-like 2 (LOXL2), a member of the lysyl oxidase (LOX) family, is a copper-dependent enzyme that catalyzes oxidative deamination of lysine residues on protein substrates. LOXL2 was found to be overexpressed in esophageal squamous cell carcinoma (ESCC) in our previous research. We later identified a LOXL2 splicing variant LOXL2-delta72 and we overexpressed LOXL2-delta72 and its wild type counterpart in ESCC cells following microarray analyses. First, the differentially expressed genes (DEGs) of LOXL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Recently, another human LOXL2 variant LOXL2-delta 72, with a loss of 72 bp (nucleotides 1234-1305 of LOXL2 WT) resulting in the deletion of 24 amino acids, has been identified in esophageal cancer (Wu et al 2014), but its function and molecular mechanisms in diverse processes and diseases need to further examined. In addition, the predicted LOXL2 ⌬e13 variant from other species such as Eptesicus fuscus (big brown bat, GenBank accession No.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another human LOXL2 variant LOXL2-delta 72, with a loss of 72 bp (nucleotides 1234-1305 of LOXL2 WT) resulting in the deletion of 24 amino acids, has been identified in esophageal cancer (Wu et al 2014), but its function and molecular mechanisms in diverse processes and diseases need to further examined. In addition, the predicted LOXL2 ⌬e13 variant from other species such as Eptesicus fuscus (big brown bat, GenBank accession No.…”
Section: Discussionmentioning
confidence: 99%
“…17 In previous studies, it has been demonstrated that LOXL2 was associated with poor prognosis in a variety of tumors and that overexpression of LOXL2 can promote the invasion and metastatic activity of cancer cells. 19,22 In the current study, we used the loss-of-function and gain-of-function experiments to elucidate the role of the novel LOXL2 variant identified from TCGA HPVnegative HNSCC data. 19,22 In the current study, we used the loss-of-function and gain-of-function experiments to elucidate the role of the novel LOXL2 variant identified from TCGA HPVnegative HNSCC data.…”
Section: Discussionmentioning
confidence: 99%
“…17,39,40 In addition, several LOXL2 splice variants have been found in esophageal squamous cell carcinoma, such as the variant lacking exon 13 and the variant with a deletion of 72 nucleotides, which contribute to tumor progression by a novel molecular mechanism distinct from canonical-type LOXL2. 19,22 In the current study, we used the loss-of-function and gain-of-function experiments to elucidate the role of the novel LOXL2 variant identified from TCGA HPVnegative HNSCC data. The tumor-specific LOXL2 variant could enhance the proliferative, migratory, and invasive capacities of HPV-negative HNSCC cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cytoscape, each protein is represented as a node, and each interaction between two nodes is represented as an edge. To increase the liabilities and define the protein perturbation to a certain level, the network reconstruction was limited to the first protein neighbors (Wu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%